2015
DOI: 10.1111/nmo.12522
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pyloric sphincter pathophysiology using EndoFLIP in patients with gastroparesis

Abstract: EndoFLIP is a novel technique that can be used to assess pyloric physiologic characteristics. Early satiety and postprandial fullness were inversely correlated with diameter and CSA of the pyloric sphincter. No significant differences were seen comparing diabetic and idiopathic gastroparetics. This technology may be of benefit to help select patients with pyloric sphincter abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 20 publications
5
101
0
4
Order By: Relevance
“…At a 40 ml balloon volume, pyloric diameter did not differ between diabetic and idiopathic gastroparesis, and was not correlated to gastric emptying rate measured by scintigraphy. Symptom intensities of early satiety and postprandial fullness, measured with the Patient's Assessment of GastroIntestinal Symptoms (PAGI-SYM) questionnaire [12], were inversely correlated to pyloric diameter [11]. However, the lack of a control group is a limitation.…”
Section: Pyloric Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…At a 40 ml balloon volume, pyloric diameter did not differ between diabetic and idiopathic gastroparesis, and was not correlated to gastric emptying rate measured by scintigraphy. Symptom intensities of early satiety and postprandial fullness, measured with the Patient's Assessment of GastroIntestinal Symptoms (PAGI-SYM) questionnaire [12], were inversely correlated to pyloric diameter [11]. However, the lack of a control group is a limitation.…”
Section: Pyloric Resistancementioning
confidence: 99%
“…Malik et al [11] used the EndoFLIP to measure pyloric resistance in 54 gastroparesis patients (39 idiopathic, 15 diabetic) during endoscopy. At a 40 ml balloon volume, pyloric diameter did not differ between diabetic and idiopathic gastroparesis, and was not correlated to gastric emptying rate measured by scintigraphy.…”
Section: Pyloric Resistancementioning
confidence: 99%
“…The volume of flow through a circular opening is proportional to the opening diameter of the lumen raised to the fourth power . Recent studies reported the use of an EndoFLIP on the pylorus in human subjects . Pyloric compliance inversely correlates with gastric emptying, but no correlation between pyloric pressure and gastric emptying was reported …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported the use of an EndoFLIP on the pylorus in human subjects . Pyloric compliance inversely correlates with gastric emptying, but no correlation between pyloric pressure and gastric emptying was reported …”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, fasting pyloric compliance was found to decrease in a sub-group of gastroparetic patients, and dilation in these patients improved the quality of life scores. 34 The basal pyloric pressure was also found to be elevated in almost half of patients with nausea and vomiting and delayed gastric emptying.…”
Section: Gastroparesismentioning
confidence: 99%